Persuasive Performance Feedback: The Effect of Framing on Self-Efficacy - Choe, Eun Kyoung; Lee, Bongshin; Munson, Sean; Pratt, Wanda; Kientz, Julie A. (Proceedings of AMIA 2013, 2013)
Self-monitoring technologies have proliferated in recent years as they offer excellent potential for promoting healthy behaviors. Although these technologies have varied ways of providing real-time feedback on a user's current progress, we have a dearth of knowledge of the framing effects on the performance feedback these tools provide. With an aim to create influential, persuasive performance feedback that will nudge people toward healthy behaviors, we conducted an online experiment to investigate the effect of framing on an individual's self-efficacy. We identified 3 different types of framing that can be applicable in presenting performance feedback: (1) the valence of performance (remaining vs. achieved framing), (2) presentation type (text-only vs. text with visual), and (3) data unit (raw vs. percentage). Results show that the achieved framing could lead to an increased perception of individual's performance capabilities. This work provides empirical guidance for creating persuasive performance feedback, thereby helping people designing self-monitoring technologies to promote healthy behaviors.
Student Paper Competition Finalist